2013
DOI: 10.1016/j.mimet.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Improvements on colony morphology identification towards bacterial profiling

Abstract: Colony morphology may be an indicator of phenotypic variation, this being an important adaptive process adopted by bacteria to overcome environmental stressors. Furthermore, alterations in colony traits may reflect increased virulence and antimicrobial resistance. Despite the potential relevance of using colony morphological traits, the influence of experimental conditions on colony morphogenesis has been scarcely studied in detail. This study aims to clearly and systematically demonstrate the impact of some v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 55 publications
2
45
0
4
Order By: Relevance
“…Antagonism of yeast with microorganisms mainly occurs due to competition for nutrients, pH changes, and the production of organic acids (Buyuksirit and Kuleasan, 2014;Sigler & Höfer, 1991), in addition to mechanisms based on the secretion of antimicrobial compounds such as killer toxins. All these methods are an important area of research into natural biocontrollers of industrial interest (Hatoum et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antagonism of yeast with microorganisms mainly occurs due to competition for nutrients, pH changes, and the production of organic acids (Buyuksirit and Kuleasan, 2014;Sigler & Höfer, 1991), in addition to mechanisms based on the secretion of antimicrobial compounds such as killer toxins. All these methods are an important area of research into natural biocontrollers of industrial interest (Hatoum et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that wild strains exhibit greater antimicrobial resistance than strains of the collection because the former are exposed to various environmental factors that force them to create efficient mechanisms to adapt to the environment, making them more resistant than a strain from the collection (Davidson & Harrison, 2002;Sousa, Machado, Nicolau, & Pereira, 2013). For that reason, wild strains were not used for subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The colony model was assumed to be a spatial modulator that affects the amplitude and phase of the incident light wave . The shape of a bacterial colony is described in terms of form, elevation, margin, texture, size and color . In this paper, only the effect of the form and elevation were studied, neglecting the others.…”
Section: Methodsmentioning
confidence: 99%
“…C. albicans (ATCC10231), S. aureus (ATCC25923), P. aeruginosa (ATCC9027), and E. coli (ATCC25922) obtained from American Type Culture Collection, were cultured at 37°C in tryptic soy broth (pH 7.2, BD Diagnosis Systems, Sparks, MD) [13][14][15] . All the bacteria and yeast kept on a rotary shaker at 220 rpm were cultivated for 8 h. The concentration of cells was 10 9 CFU/ml as assessed by 600 nm absorption.…”
Section: Culture Of Microorganismsmentioning
confidence: 99%